(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2018)
The emphasis given to study music is not indisputable were some of the authors200 such as Nketia (1982), Merriam (1964), Herskovits (1948) have extensively discussed the role of music. Music has high significance in African traditional society where music is a dimension or a way of life and an avenue of expression and communication that pervades many areas of life‘ Nketia (1982). Merriam (1964) sees music as an accompaniment to or part of almost every human sphere, which can and does shape, strengthen and channel social, political, economic, linguistic, religious, and other kinds of behavior. Similarly, Herskovits (1948 in Merriam 1964) indicates that music cuts across all aspects of culture consisting of i) material culture and its sanctions, b) social institutions, c) mind and the universe, and d) aesthetic and language. It is also believed that it yields crucial information in various aspects of culture including education, social and political spheres, in reconstructing cultural history, entertainment etc.